CONTRIBUTION A L’ETUDE DE LA BIODIVERSITE VEGETALE ET SA CONSERVATION DANS LES FORETS DE LA REGION EST DE MOSTAGANEM - RAZALI, Mohamed Cherif; ABDERRAHMANE, Naima (My University, 2020)
This work concerns the study of biodiversity and its conservation in the forests of the eastern region of the Mostaganem region The contribution is focused on highlighting the value of vegetated areas as national or even international heritage and by proposing certain easy and practical solutions for the restoration or rehabilitation of degraded areas. The main objective arising from these questions and constituting the heart of our subject is the study of -verifying and clarifying the knowledge of this flora of major interest in order to consider better protection and conservation. This conservation will thus concern the natural habitats of these plants which are currently without legal status of protected areas, remain defenseless prey of the “enemies of nature”.
Keywords: plant biodiversity; coastal; conservation; Mostaganem